The impact of Saudi Arabia - United States clinical pharmacy post-graduate training programs agreements on clinical pharmacy faculty in Saudi universities: A retrospective descriptive study focused on history and future recommendations - Yazed S. Alsowaida; Ghazwa B Korayem; Abrar K Thabit; Omar A. Alshaya; Rahaf S. Alsaif; Thamer A. Almangour (Elsevier, 2024)
Background: There has been a growing demand for clinical pharmacy services in the Kingdom of Saudi Arabia (KSA) in the past 3 decades. The Ministry of Education has established agreements with several institutions in the United States to secure clinical pharmacy residency and research fellowship programs opportunities for Saudi scholars. The aims of this study were to describe the Saudi scholars' clinical pharmacy training pathways and their contribution to the pharmacy profession in KSA. Methods: This is a retrospective, descriptive study conducted on clinical pharmacy faculty in governmental Saudi universities who graduated from the US until 2023. The study outcomes included the post-graduate year-1 (PGY-1) residency match rate, post-graduate year-2 (PGY-2) acceptance rate, the PGY-2 specialties of Saudi scholars, and the number of clinical pharmacy programs established in KSA. Results: In total, 115 Saudi scholars have pursued clinical pharmacy pathway in the US. The PGY-1 residency match rate was 80 % (92/115). In contrast, the PGY-2 acceptance rate was 60.9 % (70/115). The most common PGY-2 specialty was in infectious diseases (N = 17; 24 %). Two pharmacy colleges had established residency programs and 1 pharmacy college had established a research fellowship. Conclusion: The Ministry of Education's efforts for clinical pharmacy program agreements were fundamental for advancing clinical pharmacy in Saudi universities. A significant number of Saudi scholars returned to KSA with clinical pharmacy degrees. There are more opportunities for further development, including expanding the clinical pharmacy program collaboration in the US and increasing the number of residency and research fellowship positions in KSA.